Design and implementation of personal health data monitoring and retrieval system for health providers - Ojo-Seriki, D. F. (Vaal University of Technology, 2020)
Personal health record system (PHRS) is a tool that is used in maintaining the health and wellness of an individual as well as helping with illness of an individual. PHRS gives the individual access to a wide range of credible health information, data, and knowledge. Individuals can use that access to improve their health and manage their diseases. Patients with chronic illness can track and manage their health in conjunction with their health provider, this will promote early intervention when they encounter an abnormality or complications. Continuous monitoring and storing of health information has been a challenge for patients and health providers. Personal health data monitoring and retrieval system for health providers was designed and implemented. The main aim of this study was to develop an accurate, secure and flexible personal health data monitoring and retrieval system for health providers (PHRS). This was achieved. The research showed that when a patient health information (Electrocardiogram (ECG) and temperature) was monitored, the heartbeat (ECG) sensor output the value as an analog value to the signal processing (NodeMCU) which was then converted to a digital value. The temperature sensor used in this research is a digital sensor which lowers the amount of ADC conversion that was done. The digital values are displayed on LCD, its send to a personal health data storage system which was designed for health information storage purposes. It also sends the value to a retrieval system which is an android application that is connected to the data storage system to display health information to the health providers from a remote location. Personal health data storage and the retrieval system are secure due to the Message queuing telemetry transport (MQTT) protocol used in the application layer. The MQTT protocol is secure due to the secure socket layer (SSL) which is an encryption based on presentation layer embedded inside the MQTT protocol. After the comparison of the software simulation and the prototype test, the differences in the value for the heartbeat and temperature sensor indicate 0.04 BPM and 0.04 oC which shows the accuracy of the sensing circuit. Personal health data monitoring and retrieval system developed is applicable and useful to multiple entities in and around South Africa such as; Ministry of health, hospitals, sport and recreations.
M. Tech. (Department of Process Control and Computer System: Electrical Engineering, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Personal health record system; Personal health data monitoring; Retrieval system; Health providers; Storing of health information; Dissertations, Academic -- South Africa.; Medical records.; Information storage and retrieval systems -- Medical care.; Internet of things.; Electronic mail systems.